OP0065 THE VERY EARLY DIAGNOSIS OF SYSTEMIC SCLEROSIS (VEDOSS) PROJECT: PREDICTORS TO DEVELOP DEFINITE DISEASE FROM AN INTERNATIONAL MULTICENTRE STUDY. (June 2019) - Randone, Silvia Bellando; Lepri, Gemma; Husher, Dorte; Minier, Tunde; Guiducci, Serena; Bruni, Cosimo; Czirják, László; Cutolo, Maurizio; Smith, Vanessa; Avouac, Jérôme; Furst, Daniel; Allanore, Yannick; et al.
Abstract : Background: Early identification of patients is of key importance for the management and treatment of inflammatory rheumatic diseases. Objectives: The aim of the VEDOSS project (1) is to determine through an at-risk population the predictive factors for the progression toward a definite systemic sclerosis (SSc). Methods: VEDOSS investigators prospectively recruited patients with Raynaud phenomenon (RP), with or without anti-nuclear antibodies (ANA)for this longitudinal, observational study. Fulfilling the 2013 classification criteria at baseline was an exclusion criterion. Patients with primary Raynaud syndrome were recruited as controls. Patients had an annual assessment according to EUSTAR standards to determine organ involvement and severity. The endpoint was defined as fulfilment of the 2013 classification criteria. The time to fulfilling 2013 classification criteria was evaluated with Kaplan-Meier analysis, and predictors of evolution were determined by univariate and multivariate Cox regression. Results: 735 patients with RP were recruited into the study. The sample is distributed as follows: i) 237 patients (143 with follow up) RP/ANA negative (ANA - /pRP) as the control group, ii) 498 patients (401 with follow up) RP/ANA positive (ANA + /pRP)): 87 had puffy fingers (PF), 199 had anti-centromere antibodies (atb) positive, 45 had anti-topoisomerase I atb positive and 182 had nailfold videocapillaroscopy (NVC) abnormalities at baseline. Out of 401 ANA + /pRP patients, 7.4% within 1 year, 29.3% within3 and 44.1% within 5 years satisfied the 2013 classification criteria. Out of the 143 ANA - /pRP patients, none (0%) within 1 year, 4.6% within 3 years, and 4, 6% within 5 years satisfied SSc criteria. After adjustment for age, the following baseline parameters were identified as independent predictors for progression into definite SSc by multivariate analysis: puffy fingers (OR=3.4 [2.0;5.6]), anti-centromere atb (OR=2.6 [1.6;4.1]) and anti-topoisomerase 1 atb (OR=3.1 [1.6;5.8]), and NVC abnormalities (OR=1.9 [1.3;2.9]) The presence of PF had a positive predictive value (PPV) of 79% and combination of PF + specific auto-antibodies showed 94% PPV to satisfy ACR/EULAR 2013 criteria within 5 years (figure 1). Conclusion: the data show that patients with very early SSc develop definite, classification criteria fulfilling SSc within 5 years of follow up. The VEDOSS study identified PF and SSc auto-antibodies at first visit as independent parameters predicting the development of definite SSc. These data are of key importance for the risk stratification of patients with very early SSc in clinical practice and clinical studies. Reference: [1] Avouac J, et al. Ann Rheum Dis2011;70:476 Disclosure of Interests: Silvia Bellando Randone: None declared, Gemma Lepri: None declared, Dorte Husher: None declared, Tunde Minier: None declared, Serena Guiducci: None declared, Cosimo Bruni: None declared, László Czirják: None declared, Maurizio Cutolo: None declared, Vanessa Smith: None declared, Jérôme Avouac Grant/research support from: research grant from Pfizer, Daniel Furst Grant/research support from: F. Hoffmann-La Roche, Genentech, Yannick Allanore Grant/research support from: Inventiva, F Hoffman La-Roche, Sanofi, BMS, Pfizer, Consultant for: Actelion, Bayer, BMS, Boehringer, Roche, Sanofi, Oliver Distler Grant/research support from: Prof. Distler received research funding from Actelion, Bayer, Boehringer Ingelheim and Mitsubishi Tanabe to investigate potential treatments of scleroderma and its complications, Consultant for: Prof. Distler has/had consultancy relationship within the last 3 years with Actelion, AnaMar, Bayer, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Italfarmaco, iQvia, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Serodapharm and UCB in the area of potential treatments of scleroderma and its complications. In addition, he had/has consultancy relationship within the last 3 years with A. Menarini, Amgen, Abbvie, GSK, Mepha, MSD, Pfizer and UCB in the field of arthritides and related disorders, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Pfizer, BMS, Chemomab, Sanipedia, Speakers bureau: Actelion, BMS; MSD, Janssen